Regioselective O-acylation of myo-inositol 1,3,5-orthoesters: dependence of regioselectivity on the stoichiometry of the base - Sureshan, Kana M.; Devaraj, Subramanian; Shashidhar, Mysore S. (Tetrahedron, 2009)
A metal mediated unusual 1-3 acyl migration from C4-O to C2-OH of myo-inositol 1,3,5-orthoformate was observed during the alkylation of racemic 4-O-benzoyl-myo-inositol 1,3,5-orthoformate. This has been exploited for the selective esterification of either the C4(6)-OH or the C2-OH of myo-inositol by varying the amount of the base used. While the use of 1 equiv of the base (sodium hydride or potassium tert-butoxide) for the acylation of myo-inositol orthoesters gives the corresponding C4-ester exclusively, the use of two or more equivalents of base for the same reaction gives the C2-ester exclusively. The relatively higher stability of the alkoxide of racemic 2-O-acyl-myo-inositol 1,3,5-orthoester as compared to the alkoxide of 4-O-acyl-myo-inositol 1,3,5-orthoester is suggested to be responsible for the observed isomerization. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Cyclitol; Inositol; Orthoester; Regioselectivity; transesterification

Relative reactivity of hydroxyl groups in inositol derivatives: role of metal ion chelation - Devaraj, Subramanian; Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Carbohydrate Research, 2009)
O-Alkylation of myo-inositol derivatives containing more than one hydroxyl group via their alkali metal alkoxides (sodium or lithium) preferentially occurs at a hydroxyl group having a vicinal cis-oxygen atom. In general the observed selectivity is relatively higher for lithium alkoxides than for the corresponding sodium alkoxide. The observed regioselectivity is also dependent on other factors such as the solvent and reaction temperature. A perusal of the results presented in this article as well as those available in the literature suggests that chelation of metal ions by inositol derivatives plays a significant role in the observed regioselectivity. Steric factors associated with the axial or equatorial disposition of the reacting hydroxyl groups do not contribute much to the outcome of these O-alkylation reactions. These results could serve as guidelines in planning synthetic strategies involving other carbohydrates and their derivatives. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbohydrate; Chelation; Cyclitol; Inositol; Protecting group

Radical mediated deoxygenation of inositol benzylidene acetals: conformational analysis, DFT calculations, and mechanism - Gurale, Bharat P.; Vanka, Kumar; Shashidhar, Mysore S. (Carbohydrate Research, 2012)
Xanthates of 1,3-benzylidene acetal derivatives of myo- and neo-inositols undergo dideoxygenation under Barton-McCombie conditions, as a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Scrutiny of structure of these bicyclic inositol derivatives shows that although the conformation of the two rings can vary depending on the configuration of the inositol ring and the phase in which the molecules are present, both the xanthates lead to the formation of the same dideoxyinositol. DFT calculations on these molecular systems suggest that neo-inositol derivatives undergo conformational change prior to radical formation while myo- inositol derivatives undergo conformational change subsequent to radical formation, during the deoxygenation reaction. A low barrier for intramolecular hydrogen transfer supports the extreme facility of this deoxygenation reaction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Deoxygenation; DFT; Inositol; Mechanism; Radical; Xanthate